Pengembangan Kompetensi Sumber Daya Manusia Pada Dinas Pariwisata Kabupaten Maluku Tenggara - Reyaan, Edmundus; Rengifurwarin, Zainal Abidin; Ohuiwutun, Stanislaus K.; Selanno, Hendry; Rejaan, Silvius; Renwarin, Martinus (LPPM Institut Pendidikan Nusantara Global, 2024)
The development of human resources competencies in the Tourism Department of Maluku District of the South has been done for this time, as a whole has been realized quite well, but from the implementation process has not achieved optimal results, there is a need for improvement in order to maximum results. Overall the results of the research achievement imply for the development of the human resource competence in the tourism department in Maluku County the South according to the sociogram of priorities that have been empirically realized as a follow-up process through the internal consensus of the organization in forming a special format for development of competence human resources in tourism Department Maluku Districts of the south.